2009
DOI: 10.1097/ajp.0b013e3181a5b665
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Epidural Fibrosis

Abstract: A statistical comparison of the clinical picture in the 2 surgically treated groups failed to reach statistical significance. Nevertheless, a trend toward better clinical picture in the steroid mix group was observed. Paradoxically, when statistically compared, the rate of EF build-up was found greater in the steroid-treated group. A 5% statistical significance was established in the correlation between the presence of EF and the patients' subjective rating (difference between input and output visual analog sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 16 publications
0
13
0
2
Order By: Relevance
“…Proliferation of dura mater/fibrous tissue following surgical intervention has been well documented with post-surgical epidural fibrosis, as well as in craniotomies with either no sealant or PEG or alginate based sealants (Masopust et al, 2009; Nunamaker and Kipke, 2010; Preul et al, 2003). It has also been reported that fibrous encapsulation of epidurally implanted silicone electrocorticography grids with no sealant can occur as quickly as one week, with fibrous tissue ultimately between 300-700 μm thick (Schendel et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Proliferation of dura mater/fibrous tissue following surgical intervention has been well documented with post-surgical epidural fibrosis, as well as in craniotomies with either no sealant or PEG or alginate based sealants (Masopust et al, 2009; Nunamaker and Kipke, 2010; Preul et al, 2003). It has also been reported that fibrous encapsulation of epidurally implanted silicone electrocorticography grids with no sealant can occur as quickly as one week, with fibrous tissue ultimately between 300-700 μm thick (Schendel et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…A fibrose peridural pode fixar as raízes e a dura-máter aos tecidos circundantes, comprometendo a nutrição e a atividade dinâmica do segmento; a alteração de fluxos arteriais e venosos de estruturas sensíveis à deformação mecânica, como o gânglio da raiz dorsal, tem impacto clínico considerável, manifestando-se com dor, paresia e parestesias (43) . O ligamento amarelo forma uma barreira anatômica para as raízes, dura-máter e gordura epidural, protegendo essas estruturas da compressão causada pelos tecidos circundantes; por isso, a sua preservação pode resultar em melhor prognóstico em relação à formação de fibrose epidural pós-discectomia (44) .…”
Section: Preservação Do Ligamento Amarelounclassified
“…1,2,4 Epidural fibrosis is mentioned in the literature as a common cause of pain after lumbar spine surgery and has been implicated in 8% to over 60% of cases of "failed back surgery syndrome" (FBSS), [3][4][5][6][7] despite several studies refuting any association. [8][9][10][11][12] Moreover, recent literature suggests that magnetic resonance imaging (MRI) may not be the most sensitive method for the diagnosis of epidural fibrosis. Using epiduroscopy as a diagnostic method, Bosscher and Heavner report severe fibrosis in 83% of their patients with persistent or recurrent symptoms after lumbar surgery.…”
Section: Introductionmentioning
confidence: 99%